A new highly sensitive enzyme-linked immunosorbent assay for the detection of Plasmodium falciparum histidine-rich protein 2 in whole blood - Ihn Kyung Jang; Smita Das; Rebecca S. Barney; Roger B. Peck; Andrew Rashid; Stephane Proux; Emmanuel Arinaitwe; John Rek; Maxwell Murphy; Katherine Bowers; Samuel Boadi; Julie Watson; et al. (Malaria Journal, 2018)
Abstract Background The detection of submicroscopic infections in low prevalence settings has become an increasingly important challenge for malaria elimination strategies. The current field rapid diagnostic tests (RDTs) for Plasmodium falciparum malaria are inadequate to detect low-density infections. Therefore, there is a need to develop more sensitive field diagnostic tools. In parallel, a highly sensitive laboratory reference assay will be essential to evaluate new diagnostic tools. Recently, the highly sensitive Alere™ Malaria Ag P.f ELISA (HS ELISA) was developed to detect P. falciparum histidine-rich protein 2 (HRP2) in clinical whole blood specimens. In this study, the analytical and clinical performance of the HS ELISA was determined using recombinant P. falciparum HRP2, P. falciparum native culture parasites, and archived highly pedigreed clinical whole blood specimens from Karen village, Myanmar and Nagongera, Uganda. Results The HS ELISA has an analytical sensitivity of less than 25 pg/mL and shows strong specificity for P. falciparum HRP2 when tested against P. falciparum native culture strains with pfhrp2 and pfhrp3 gene deletions. Additionally, the Z′-factor statistic of 0.862 indicates the HS ELISA as an excellent, reproducible assay, and the coefficients of variation for inter- and intra-plate testing, 11.76% and 2.51%, were acceptable. Against clinical whole blood specimens with concordant microscopic and PCR results, the HS ELISA showed 100% (95% CI 96.4–100) diagnostic sensitivity and 97.9% (95% CI 94.8–99.4) diagnostic specificity. For P. falciparum positive specimens with HRP2 concentrations below 400 pg/mL, the sensitivity and specificity were 100% (95% CI 88.4–100) and 88.9% (95% CI 70.8–97.6), respectively. The overall sensitivity and specificity for all 352 samples were 100% (CI 95% 96–100%) and 97.3% (CI 95% 94–99%). Conclusions The HS ELISA is a robust and reproducible assay. The findings suggest that the HS ELISA may be a useful tool as an affordable reference assay for new ultra-sensitive HRP2-based RDTs.